The Pattern of Abdi Dalem Communication in Improving Cultural Values in The Duchy of Pakualaman - Astari, Devi Wening; Sekarningrum , Anggun Anindya (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
Amid today's modernization, communication between courtiers is essential in developing cultural values in the Kadipaten Pakualaman environment. This research aims to determine communication patterns in the Pakualaman Duchy environment in maintaining and developing traditional Javanese cultural values. This research is a qualitative descriptive research. Data was collected through interviews, observation, Focus Group Discussion (FGD), and documentation. Data were analyzed using qualitative descriptive analysis techniques. This research shows that Abdi Dalem's communication patterns are starting to experience openness, which can be seen from the maintenance of cultural values in Kadipaten Pakualaman, using Fine Javanese (krama) and Indonesian. Abdi Dalem's communication patterns in the Kadipaten Pakualaman environment include openness, speed, use of communication media tailored to needs, communication using verbal and non-verbal language, and maintaining good manners.